1999
DOI: 10.1136/ip.5.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional injury mortality in children: a priority for middle income countries in the advanced stage of epidemiological transition

Abstract: Objectives-To examine the relationship between the magnitude, and the relative importance of unintentional child injury mortality with socioeconomic development, and to conceptualise the dynamic changes in injury mortality within the framework of epidemiological transition. Design-Ecological cross sectional study using data on 51 countries. Main outcome measures-The relationship between total mortality rates, unintentional injury mortality rates, and percentage in children 1-14 years of age with gross national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
3
16
1
2
Order By: Relevance
“…Estudos ecológicos identificaram correlação negativa entre o Produto Interno Bruto de 51 países e as injúrias não intencionais envolvendo crianças de 5 a 14 anos, apesar de não ocorrer em todos os extratos sociais 27 . Estudos europeus identificam a crescente diferença social como um fator de aumento das injúrias e de seu impacto nas condições de vida nesses países 28 .…”
Section: As Populações Vulneráveisunclassified
“…Estudos ecológicos identificaram correlação negativa entre o Produto Interno Bruto de 51 países e as injúrias não intencionais envolvendo crianças de 5 a 14 anos, apesar de não ocorrer em todos os extratos sociais 27 . Estudos europeus identificam a crescente diferença social como um fator de aumento das injúrias e de seu impacto nas condições de vida nesses países 28 .…”
Section: As Populações Vulneráveisunclassified
“…178 Studies from Sweden have shown that large socio-economic differences within a country predispose for higher child mortality. 45,124 For example, the US and Bulgarian unintentional child mortality rates were found to be equal, even though the US gross national product per inhabitant is 30 times higher. Sweden had "the best results" in 2001 with only 5.2 deaths per 100,000 children.…”
Section: Child Injuries In Perspective 61 the Global And National Simentioning
confidence: 99%
“…27 European studies have pointed out growing social discrepancy as the cause for the increase in the number of injuries and for their impact on the quality of life in Europe. 28 Vulnerable social groups and individuals are at higher risk for unintentional injuries.…”
Section: Vulnerable Populationsmentioning
confidence: 99%